The nasciturus non-fiction: the Libby Gonen story: contemporary reflections on the status of nascitural personhood in South African law - Schulman, Marc (My University, 2014)
The non-consensual destruction of a nasciturus is a disturbing societal phenomenon that negatively permeates the lived realities of pregnant women with positive maternal intention. These women choose to experience a full term gestation and they choose to give birth to a live and healthy infant. At some point during their gestation they are non-consensually deprived of their choices through active third party violence by commission or passive third party negligence by omission. These women have no legal recourse for their loss, because in South African law, the non-consensual destruction of a nasciturus is not a crime. The nasciturus is not recognised as a victim separate from the pregnant woman despite the manner in which the pregnant woman freely chooses to interpret her pregnancy. The consensual destruction of a nasciturus enjoys legal protection in South African law by virtue of the provisions contained in the Choice on Termination of Pregnancy Act 92 of 1996. The choice to terminate a pregnancy is therefore legally recognised in South African law, whereas the choice to continue a pregnancy is not legally recognised. Argument is advanced in this dissertation for the legal recognition of the choice to continue a pregnancy by criminalising non-consensual nascitural destruction through the creation of a Choice on Continuation of Pregnancy Act. Non-Consensual nascitural destruction occurs as a result of violence against pregnant women as well as in situations of medical negligence. Empirical data is provided to demonstrate how non-consensual nascitural destruction can occur in medical settings where negligence is suspected. The inherent human need to safeguard and protect the nasciturus has been in existence since time immemorial. Despite this need, in South African law, legal subjectivity, and the ability to be recognised as a separate victim of crime, remain contingent upon a live birth. Evidence suggests that the requirement of live birth in law developed as an evidentiary mechanism and not as a substantive rule of law. Its relevance in circumstances of non-consensual nascitural destruction is doubtful at best. The law in South Africa has failed to take cognisance of the psychosomatic dimensions of personhood and argument is advanced in favour of a nuanced and constitutionally sensitive approach to matters of moral as well as legal personhood. Authentic female autonomy and reproductive freedom requires a re-evaluation of the paradigms that surround nascitural safeguarding and protection, and a transformative approach to constitutional interpretation. The establishment of a legislative scheme to criminalise the nonconsensual destruction of a nasciturus is proposed. Within this legislative scheme certain precautions and fortifications are suggested in order to avoid any potential erosion of the rights of pregnant women who have negative maternal intention. It is demonstrated that it is in fact possible for pregnant women with positive maternal intention and pregnant women with negative maternal intention to both enjoy legal protection without encroaching upon one another’s constitutional rights to reproductive freedom, bodily autonomy and privacy. It is contended that achieving the aforementioned is the final barrier to authentic female reproductive freedom in South Africa.
Thesis (L.L.M.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2014.
Keywords: Unborn children (Law); Fetus--Legal status, laws, etc.--South Africa; Pregnant women--Legal status, laws, etc.--South Africa